The Impact Of Excessive Smartphone Use On Productivity And Completion Of Academic Tasks - Grecia Angelika Nainggolan (Journal of Smart Education and Emerging Technology, 2026)
Background/Context: The rapid development of digital technology has made smartphones an inseparable part of students' daily lives, both for academic and entertainment purposes, potentially leading to excessive use that may affect learning effectiveness and productivity. Objective/Purpose: This study aims to analyze the impact of excessive smartphone use on students' productivity and the completion of academic tasks. Method: This study employed a quantitative approach with a survey design, involving 33 respondents selected using a non-probability sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, and analyzed using descriptive statistics and simple linear regression. Results: The results indicate that excessive smartphone use does not have a statistically significant effect on students' productivity or the completion of academic tasks. Conclusion: Although no significant effect was found, effective and responsible smartphone use remains important to support optimal academic performance and minimize potential distractions.